Coagulation parameters as predictors of DIC in patients with intact aortic aneurysm - Jeleńska, M. M. (Hämostaseologie, 2004)
Clinically overt, preoperative, disseminated intravascular coagulation (DIC) is not common in patient with aortic aneurysm. However, cases with large and expanding aneurysm are especially prone for this coagulopathy. Contrary to the clinically overt form compensated DIC in patients with aortic aneurysm seems frequent and is probably underdiagnosed. The compensated DIC may be recognized, even without bleedings, by laboratory tests documenting the activated coagulation and fibrinolysis. We show that in about one third of patients with abdominal aorta aneurysm (AAA) compensated DIC can be identified. This enables the application of preoperative anticoagulation treatment to improve the intraoperative haemostasis.
Keywords: DIC; aortic aneurysm; coagulation